Expanding the Horizontal Call: A Typology of Social Influence on the Call to Ministry - Johnston, Erin F. ca. 20./21. Jh. (Journal for the scientific study of religion, 2023)
This research examines the social actors and interactions that facilitate seminary students' sense of calling. Drawing from 36 in-depth interviews with first year Masters of Divinity students, we introduce six ideal typical social others who play a formative role in the early stages of a call to ministry: instigators, exemplars, interpreters, affirmers, challengers, and codiscerners. Together, these findings demonstrate that the call to ministry, while deeply personal, emerges through social interactions that facilitate and make plausible a person's sense of calling and that sustain it over time. Extending Richard Pitt's conceptualization of the “horizontal call,” this paper argues that social others help evoke and solidify—not merely legitimate—a personal sense of call. This research also highlights differences in the social structuring of call by gender. Despite considerable gains in the ordination of women, we find that many still face obstacles to experiencing and embracing a call to ministry.